The First Report of Ruminant Fascioliasis in Sabah, East Malaysia - Naim Che Kamaruddin; Muhammad Ali Imran Razali; Ibitoye Emmanuel Busayo; Noor Hazfalinda Hamzah; Lokman Hakim Idris; Nur Mahiza Md Isa (Journal of Parasitology Research)
Ruminant fascioliasis is a neglected yet important tropical zoonotic disease that affects both the livestock and humans. The disease has a worldwide distribution, and Malaysia is one of the countries that face problems related to this parasite. These retrospective studies were conducted in Makmal Diagnosa Veterinar Kota Kinabalu (MDVKK) and Sabah Meat Technology Centre (SMTC), Kinarut over a period of eleven years (2008–2018). For MDVKK, the overall occurrence of fascioliasis was 24.9%. Out of 769 cattle’s and buffaloes’ faecal samples submitted, Fasciola spp ova were detected in 189 of the samples. A total of 2297 cattle, buffaloes, and goats were slaughtered at SMTC over that period, and 21 livers were condemned due to fascioliasis, giving the total occurrence of 0.91%. This investigation provides information on the occurrence of ruminant fascioliasis in Sabah, East Malaysia. The results from this study highlight the alarming incidence of fascioliasis and the urgent need for action to control this neglected tropical disease in East Malaysia.